Context and Continuity - Universal Versus Situational in Architecture - Juhani Pallasmaa (Oz, 1985)
In Poetics of Music, Igor Stravinsky, the arch-modernist of music - whom one would expect to have fought for the cause of liberating music from its classical rules - surprisingly reveals a suspicion of modernity and a deep reverence for tradition…